Placental baseline conditions modulate the hyperoxic BOLD-MRI response. (January 2018) - Sinding, Marianne; Peters, David A.; Poulsen, Sofie S.; Frøkjær, Jens B.; Christiansen, Ole B.; Petersen, Astrid; Uldbjerg, Niels; Sørensen, Anne
Abstract: Objectives: Human pregnancies complicated by placental dysfunction may be characterized by a high hyperoxic Blood oxygen level-dependent (BOLD) MRI response. The pathophysiology behind this phenomenon remains to be established. The aim of this study was to evaluate whether it is associated with altered placental baseline conditions, including a lower oxygenation and altered tissue morphology, as estimated by the placental transverse relaxation time (T2*). Method: We included 49 normal pregnancies (controls) and 13 pregnancies complicated by placental dysfunction (cases), defined by a birth weight < 10th percentile in combination with placental pathological signs of vascular malperfusion. During maternal oxygen inhalation, we measured the relative ΔBOLD response ((hyperoxic BOLD – baseline BOLD)/baseline BOLD) from a dynamic single-echo gradient-recalled echo (GRE) MRI sequence and the absolute ΔT2* (hyperoxic T2*– baseline T2*) from breath-hold multi-echo GRE sequences. Results: In the control group, the relative ΔBOLD response increased during gestation from 5% in gestational week 20 to 20% in week 40. In the case group, the relative ΔBOLD response was significantly higher (mean Z-score 4.94; 95% CI 2.41, 7.47). The absolute ΔT2*, however, did not differ between controls and cases (p = 0.37), whereas the baseline T2* was lower among cases (mean Z-score −3.13; 95% CI -3.94,  −2.32). Furthermore, we demonstrated a strong negative linear correlation between the Log10 ΔBOLD response and the baseline T2* (r = −0.88, p < 0.0001). Conclusion: The high hyperoxic ΔBOLD response demonstrated in pregnancies complicated by placental dysfunction may simply reflect altered baseline conditions, as the absolute increase in placental oxygenation (ΔT2*) does not differ between groups. Highlights: The placental oxygen environment can be assessed non-invasively using T2*-weighted MRI. Changes in placenta BOLD signal reflect changes in placental oxygenation during maternal oxygen-challenge. In the dysfunctional placenta, the relative oxygen-challenge ΔBOLD response is higher than in the normal placenta. This increased ∆BOLD response may simply reflect altered placental baseline conditions including reduced oxygenation.